2018
DOI: 10.4103/jovr.jovr_31_17
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological parameters in pterygia and significant clinical correlations

Abstract: Purpose:To evaluate the clinical and histopathological parameters of pterygium to determine significant correlations between parameters that can affect management strategies.Methods:A total of 47 pterygia were clinically examined and excised for histopathological evaluation of epithelial and stromal changes. Some samples were immunostained with P53 (a protein of 53 kilodalton used as dysplastic epithelial marker), CD20 (CD/cluster of differentiation, are group of surface receptors providing targets for cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…7,22 Moreover, the levels of these pathogenic factors may be correlated with the clinical features of the pterygium. 23,24 There might be several reasons why primary pterygium was not shown to be associated with ECD decrease in our study. Firstly, the UV exposure in our patients might not have reached the threshold to cause ECD decrease.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…7,22 Moreover, the levels of these pathogenic factors may be correlated with the clinical features of the pterygium. 23,24 There might be several reasons why primary pterygium was not shown to be associated with ECD decrease in our study. Firstly, the UV exposure in our patients might not have reached the threshold to cause ECD decrease.…”
mentioning
confidence: 58%
“…It has been shown that pterygia with at least intermediate fleshiness, redness and extent have higher expression of extracellular matrix modulators 23 and chronic inflammation in the corneal stroma. 24 The eyes in our population may not have these clinical features and thus not induce the inflammatory changes that may be associated with ECD reduction. Thirdly, UV radiation may cause an ECD decrease in both eyes of patients, irrespective of pterygium development.…”
mentioning
confidence: 91%
“…Pterygium with intermediate fleshiness was shown had higher expression of extracellular matrix modulators [21]. Pterygium with intermediate redness and extent were also shown to have higher levels of chronic inflammation in the corneal stroma [22]. The eyes in our studies might have relatively small and less fresh pterygium since cataract surgery was indicated to these eyes.…”
Section: Discussionmentioning
confidence: 90%
“…These modulators have been shown to be expressed in pterygium tissue or the cornea underlying or adjacent to the pterygium [7, 20]. Moreover, the levels of these pathogenic factors may be correlated with the clinical features of the pterygium [2122].…”
Section: Discussionmentioning
confidence: 99%
“…Finding appropriate pharmacological therapy options for patients who do not wish to undergo surgery is a significant priority. [27] It is hoped that some non-surgical treatment methods and prophylactic procedures will soon be introduced.…”
Section: Discussionmentioning
confidence: 99%